Analisis Perilaku Konsumsi Mahasiswa Ditinjau Dari Motif Bertransaksi (Studi Kasus pada Mahasiswi S1 Pendidikan Ekonomi Fakultas Ekonomi Universitas Negeri Malang Angkatan Tahun 2012) - Niati Lisma; Agung Haryono (Universitas Negeri Malang, 2016)
Student consumption activities Prodi Economic Education in addition to the purposes of study, consumption activities are also carried out to support the appearance. This research aims to discover (1) how is the motive of the transactions in the purchase of food and fashion products, (2) how the strategy to allocate the allowances of the students of Faculty of Economic Education, State University of Malang. This study uses a qualitative method with the kind of phenomenology, the snowball sampling technique. and uses snowball-sampling technique. The data was collected by doing an interview and documentation, and the data was analyzed by using data reduction, data presentation, and conclusion/verification. The results of this research are, firstly, motif transaction in the purchase of a meal, the students of Faculty of Economic Education choose where to eat certain then documented and published in social media, Secondly, motif transaction in the purchase of fashion products, there is a student who is often influenced by friends, trends, brand, advertising and discounts. Thirdly, there are students who create a list for their consumption planning, and there are students who do not in allocating their allowances as the strategies used by the students of Faculty of Economic Education.Keywords: consuming behavior, transaction motives, students of Economic Education.